Cav3.2 T-Type Calcium Channels Are Physiologically Mandatory for the Auditory System. (15th June 2019) - Lundt, Andreas; Seidel, Robin; Soós, Julien; Henseler, Christina; Müller, Ralf; Bakki, Maheshwar; Arshaad, Muhammad Imran; Ehninger, Dan; Hescheler, Jürgen; Sachinidis, Agapios; Broich, Karl; Wormuth, Carola; et al.
Abstract: Voltage-gated Ca 2+ channels (VGCCs) play key roles in auditory perception and information processing within the inner ear and brainstem. Pharmacological inhibition of low voltage-activated (LVA) T-type Ca 2+ channels is related to both age- and noise induced hearing loss in experimental animals and may represent a promising approach to the treatment of auditory impairment of various etiologies. Within the LVA Ca 2+ channel subgroup, Cav 3.2 is the most prominently expressed T-type channel entity in the cochlea and auditory brainstem. Thus, we performed a complete gender specific click and tone burst based auditory brainstem response (ABR) analysis of Cav 3.2 +/- and Cav 3.2 -/- mice, including i.a. temporal progression in hearing loss, amplitude growth function and wave latency analysis as well as a cochlear qPCR based evaluation of other VGCCs transcripts. Our results, based on a self-programmed automated wavelet approach, demonstrate that both heterozygous and Cav 3.2 null mutant mice exhibit age-dependent increases in hearing thresholds at 5 months of age. In addition, complex alterations in WI-IV amplitudes and latencies were detected that were not attributable to alterations in the expression of other VGCCs in the auditory tract. Our results clearly demonstrate the important physiological role of Cav 3.2 VGCCs in the spatiotemporal organization of auditory processing in young adult mice and suggest potential pharmacological targets for interventions in the future. Highlights: Cav 3.2 +/- and Cav 3.2 -/- mice exhibit increased ABR thresholds upon click stimulation. Cav 3.2 +/- and Cav 3.2 -/- mice display altered tone burst evoked ABR thresholds. Cav 3.2 transgenic mice show altered amplitude growth function and wave latencies. Cav 3.2 calcium channels are mandatory for auditory information processing in adult mice.